2015
DOI: 10.1177/0148607115587949
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Administration After Sublethal Lower Limb Ischemia Reduces Inflammatory Reaction and Offers Organ Protection in Ischemia/Reperfusion Injury

Abstract: A single dose of GLN administration immediately after sublethal lower limb ischemia reduces the inflammatory reaction locally and systemically; this may offer local and distant organ protection in hind limb IR injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…This suggests that the impairment of pulmonary gas exchange was not independent of oxidative stress injury and that lipid emulsion administration reduced lipid peroxidation in muscle tissues. Our results are in agreement with somef reports [1, 8], but contrary to the reports of others [5, 14]. The reasons for the discordance between these two kinds of different reports may be related to animal species, the duration of ischemia and/or reperfusion.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This suggests that the impairment of pulmonary gas exchange was not independent of oxidative stress injury and that lipid emulsion administration reduced lipid peroxidation in muscle tissues. Our results are in agreement with somef reports [1, 8], but contrary to the reports of others [5, 14]. The reasons for the discordance between these two kinds of different reports may be related to animal species, the duration of ischemia and/or reperfusion.…”
Section: Discussionsupporting
confidence: 86%
“…Shih et al [1] reported that an excessive production of inflammatory cytokines (TNF-α, IL-1β, IL-6) may lead to the activation of neutrophils and the upregulation of CAMs on both neutrophils and endothelial cells. This is followed by transmigration into the local tissue interstitium resulting in local tissue damage, as well as an intense inflammatory responses that occur both locally and systemically [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-1 is an acute inflammatory factor that is involved in the process and regulation of ischemia-reperfusion injury. Shih et al established a mouse model of limb ischemia-reperfusion injury and found that IL-1 mRNA expression in blood was significantly increased at 4 hours after reperfusion [ 22 ]. Our study also found that IL-1 levels were significantly increased at 6 hours after reperfusion in the I/R group and that TEAS could significantly reduce this.…”
Section: Discussionmentioning
confidence: 99%